Thermoplastic polymer structures and methods for making same - Patents.com
Patent Information
- Application Number
- JP2023538050
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-21
- Filing Date
- 2021-12-20
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 00000016_0000
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Provisional Application No. 63 / 128,632, filed December 21, 2020, the entire disclosure of which is incorporated herein by reference in its entirety for all purposes. [Background technology]
[0002] Thermoplastic polymers such as thermoplastic polyurethanes (TPUs) are used as materials for a wide variety of products such as windows and flooring, especially for their high tensile and tear strength, high flexibility at low temperatures, and very good abrasion and scratch resistance. The specific composition of the TPU layers, which are often provided as layers, can be modified for their specific application. For example, polymer films used in automotive glass can be modified to prevent shattering. Furthermore, polymer films used in bulletproof glass can be tailored to improve flexibility and strength. Furthermore, polymer films used in flooring can be tailored to resist scratches and stains. While these TPU films have shown considerable promise, it would be desirable to improve certain physical properties of the TPU films, such as stiffness, toughness, durability, and / or strength, etc. It would be particularly desirable to improve these properties without substantially changing other properties of the polymer structure. Summary of the Invention
[0003] Thermoplastic polymer (TPU) compositions or structures are provided that may be bonded to other layers for certain applications, such as windows, roofs, flooring, walls, facades, and the like, to improve flexibility, strength, stiffness, toughness, and / or durability, resist shattering, increase abrasion and wear resistance, and / or resist scratching and staining. In one embodiment, the composition comprises a TPU and a second component in an amount ranging from about 3% to about 60% by weight of the composition. The second component comprises at least one reactive diluent, monomer, or oligomer (RDMO). The second component provides the TPU with improved physical properties, such as stiffness and strength. The second component may be crosslinked to form a semi-interpenetrating polymer network. The second component and the TPU may be crosslinked together to form an interpenetrating polymer network.
[0004] The second component may include two or more reactive diluents, monomers, or oligomers. The second component may be selected from the group consisting of monofunctional acrylates, difunctional acrylates, trifunctional acrylates, monofunctional methacrylates, difunctional methacrylates, trifunctional methacrylates, acrylates or methacrylates having 4 to 6 functional groups, pentaerythrityl triacrylate, polyhedral oligomeric silsesquioxanes, and triallyl isocyanurates. In one embodiment, the second component is about 20% by weight of the composition. The second component may include monofunctional acrylates, difunctional acrylates, trifunctional acrylates, monofunctional methacrylates, difunctional methacrylates, trifunctional methacrylates, acrylates or methacrylates having 4 to 6 functional groups, pentaerythrityl triacrylate, and triallyl isocyanurate. In one embodiment, the second component may be selected from the group consisting of 20% monofunctional acrylate, 20% difunctional acrylate, and 20% trifunctional acrylate. In one embodiment, the second component may be a methacrylate having a functionality of up to 6. In one exemplary embodiment, the second component may include 20% difunctional methacrylate. In another exemplary embodiment, the trifunctional acrylate may be pentaerythrityl triacrylate (PETA).
[0005] In another embodiment, the second component is about 5% by weight of the composition. The second component may include an inorganic silsequioxane, such as a polyhedral oligomeric silsequioxane, attached to other groups. The other groups may include organic methacrylate groups, organic isoctyl groups, organic vinyl groups, and / or active silanol functional groups. In one exemplary embodiment, the second component may include triallyl isocyanurate. For example, the second component may include 20% triallyl isocyanurate. The thermoplastic polyurethane (TPU) may be an aliphatic polyurethane, such as, for example, a polyether aliphatic polyurethane or a polyester aliphatic polyurethane. In another embodiment, the TPU may be a non-aliphatic polyurethane, such as, for example, a polyether non-aliphatic polyurethane or a polyester non-aliphatic polyurethane. The composition may include a curing agent, which may be selected from the group consisting of UV-activated photoinitiators, peroxides, and azo compounds.
[0006] In one exemplary embodiment, the curing agent may be a peroxide and may be in an amount of about 1.5% by weight. The peroxide may be 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, which has a half-life of 1 hour at 151.8° C., or di(t-butyl)peroxide, which has a half-life of 1 hour at 149.1° C., or 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, which has a half-life of 1 hour at 140.3° C. In other embodiments, the peroxide may be selected from the group consisting of 2,3-dimethyl-2,3-diphenylbutane, tert-butyl hydroperoxide, tert-amyl hydroperoxide, cumyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropyl cumyl hydroperoxide, isopropyl cumyl hydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane. It is understood that alternative curing agents to peroxides may be used, including UV-activated photoinitiators, or compounds with free radical generating reactive groups.
[0007] In another embodiment, the composition comprises a TPU and a second component. The second component comprises at least one reactive diluent, monomer, or oligomer (RDMO) in an amount that improves stiffness (e.g., stiffness modulus or elastic modulus coefficient). For example, in a particular embodiment, the composition has a Young's modulus greater than about 10, preferably at least 18.34, for a load duration of 1 second at 30°C, and a Young's modulus greater than about 3.83, preferably at least 6.58, for a load duration of about 2 months at 30°C. In yet another embodiment, the composition has a Young's modulus greater than about 3.69, for a load duration of about 1 second at 60°C, and a Young's modulus greater than about 2.39, preferably at least 2.86, for a load duration of 1 hour at 60°C. In another embodiment, the composition includes a TPU and a second component including at least one reactive diluent, monomer, or oligomer (RDMO). The second component has a glass transition temperature (T gIn some other embodiments, the second component has a T of greater than about 60 degrees Celsius, preferably greater than about 110 degrees Celsius. g may have the following structure:
[0008] In another embodiment, a laminate structure is provided, which may include a composition of a thermoplastic polyurethane (TPU) and a second component, the second component including at least one reactive diluent, monomer, or oligomer (RDMO) in an amount ranging from about 3% to about 60% by weight of the composition, and at least one other layer. In one embodiment, the composition is positioned between two other layers. In one particular aspect, the two other layers may include glass layers, and the composition forms an interlayer between the two layers of glass. There may be a release liner separating the composition interlayer and the glass layers, so that the final configuration is as follows: glass / release liner / modified TPU / release liner / glass. In another embodiment, the composition is combined into a single layer to form, for example, a roof, flooring, wall, or facade structure.
[0009] The second component may include two or more reactive diluents, monomers, or oligomers. The second component may be selected from the group consisting of monofunctional acrylates, difunctional acrylates, trifunctional acrylates, monofunctional methacrylates, difunctional methacrylates, trifunctional methacrylates, acrylates or methacrylates having 4 to 6 functional groups, pentaerythrityl triacrylate, polyhedral oligomeric silsesquioxanes, and triallyl isocyanurates. The second component may be crosslinked to form a semi-interpenetrating polymer network. The second component and the TPU may be crosslinked together to form an interpenetrating polymer network. In another aspect, a method of making a composition includes mixing a thermoplastic polyurethane (TPU) with a second component, the second component comprising at least one reactive diluent, monomer, or oligomer (RDMO) in an amount ranging from about 3% to about 60% by weight of the composition, and mixing a curing agent with the TPU and the second component.
[0010] The mixing may include melting the thermoplastic polyurethane, adding the second component thereto, and mixing the thermoplastic polyurethane and the second component. In some embodiments, the mixing may be carried out for at least 5 minutes using a mixer set at a temperature of up to about 120° C. In another embodiment, the method may further include cooling the thermoplastic polyurethane and the second component in the molten state. The curing agent is added to the modified TPU. In some embodiments, the addition of the curing agent is performed simultaneously with the addition of the second component to the thermoplastic polyurethane. In other embodiments, the curing agent is added after mixing the TPU and the second component. The method may further include mixing the TPU, the second component, and the curing agent to form a precursor to an interpenetrating or semi-interpenetrating polymer network. The curing agent may be added by gravimetric addition or blending. The method may further include curing the precursor to form an interpenetrating or semi-interpenetrating polymer network. The method may include a mixing step having a duration of at least 5 minutes and performed using a mixer.
[0011] In one embodiment, the extrudate may be formed from the thermoplastic polyurethane, the second component, and the curing agent by using an extruder and maintaining the temperature at up to about 120° C. to prevent crosslinking of the curing agent. In other embodiments, the second component may exhibit greater thermal stability, and thus the temperature may be maintained at up to about 140° C. while still preventing crosslinking. The method may include extruding the extrudate, flattening the extrudate, and cooling the flattened extrudate. The thermoplastic polyurethane, the second component, and the curing agent may be laminated and cured simultaneously.
[0012] In one embodiment, lamination can be accomplished by vacuum lamination in a vacuum laminator having top and bottom chambers at 60° C. for one cycle of 60 minutes. Alternative vacuum lamination steps known to those skilled in the art may be used. In some embodiments, the vacuum lamination step may include 10 minutes of evacuation of both the top and bottom chambers, and then the remaining time using partial atmospheric pressure to pressurize the top chamber to full atmospheric pressure while the laminate structure is maintained under vacuum in the bottom chamber, resulting in pressing and curing of the modified TPU in the laminate. In one embodiment, evacuation followed by pressing and curing may occur while maintaining full vacuum in the top and bottom chambers of the laminator for the first 10 minutes. Pressurizing and curing may occur while maintaining full atmospheric pressure from the part in the top chamber of the vacuum laminator. The drawings, which are incorporated in and constitute a part of this specification, illustrate exemplary embodiments and, together with the detailed description, serve to explain the principles of the present description. [Brief description of the drawings]
[0013] [Figure 1] 1 shows a cross-sectional view illustrating an exemplary embodiment of a laminate structure having a polymer structure between first and second layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] A thermoplastic polymer structure is provided that includes a thermoplastic polyurethane (TPU) and a second component. The second component includes at least one reactive diluent, monomer, or oligomer (RDMO) in an amount ranging from about 3% to about 60% by weight of the composition. The second component modifies the physical properties and strength of the TPU interlayer by the addition of the reactive diluent / monomer / oligomer (RDMO) to the TPU resin matrix. The thermoplastic polymer structure may be bonded to other layers for certain applications, such as windows, roofs, flooring, walls, facades, and the like, to improve flexibility, durability, stiffness, and / or strength, resist shattering, and / or resist scratching and staining. For example, glass structures with thermoplastic polymer layers may be used in vehicles, aircraft, ships, buildings, military vessels, including submarines, for protection purposes, in police stations, prisons, jails, or border facilities, in banks, embassies, or government buildings, to showcase artworks, including artworks in museums, to showcase merchandise, for use in zoos, for use in fire engines, or for use in protective helmets. In another embodiment, the thermoplastic structure may be bonded to another layer to form a roof, flooring, wall, or facade structure with improved wear and tear resistance.
[0015] In certain aspects, the structural polymer network may be an interpenetrating polymer network (IPN) or a semi-interpenetrating polymer network (semi-IPN). An interpenetrating polymer network (IPN) is a combination of two or more polymers that are not covalently bonded to each other but are polymerized or crosslinked in the presence of each other (or the bond is negligible between the two or more polymers). A semi-IPN is a polymer that includes one or more networks and one or more linear or branched polymers, characterized by molecular-scale penetration of at least one of the networks by at least a portion of the macromolecule. Some embodiments of the TPU interlayer disclosed herein are semi-IPNs due to crosslinking of RDMO by peroxide free radicals, which form chains entangled with the TPU in a double network. For example, the formation of a crosslinked TPU can include chemical bonds formed by crosslinking a polymer with a TPU that has terminal functional radical polymerizable groups at both ends of the TPU. These IPNs can provide TPUs with advantageous attributes, including improved transparency and hardness compared to TPU alone. In some embodiments, the attributes of the TPU are tailored through the selection of the RDMO: In embodiments, the stiffness and hardness of the TPU film are improved by increasing the complex chemical structure in the TPU, for example by adding an RDMO with a high glass transition temperature (Tg) and low molecular weight.
[0016] The properties of the structural TPU interlayer can be tailored through the selection of the RDMO. Attributes that affect physical strength include chemical structure, degree of functionality, molecular weight, and Tg (glass transition temperature). Applicants have discovered that complex chemical structure and increasing functionality positively impact the stiffness and strength of the structural TPU interlayer. Similarly, the higher the glass transition temperature of the RDMO, the greater the stiffness of the resulting structural TPU interlayer. The lower the molecular weight of the RDMO, the greater the strength and stiffness. FIG. 1 shows a cross-sectional view illustrating an example of a laminate structure 100 having a polymer film layer. In some embodiments, the modified TPU may be included in a laminate structure that includes the modified TPU and at least one other layer. In one embodiment, the composition is between two other layers. In one embodiment, the two other layers include glass layers. In some embodiments, the laminate structure 100 includes a first layer 110, a second layer 120, and a polymer interlayer 130 between the first layer 110 and the second layer 120. In some embodiments, the first layer 110 and the second layer 120 can be glass. For example, the first layer 110 and the second layer 120 can be automotive glass, architectural glass, or other suitable type of glass.
[0017] In some embodiments, the polymer interlayer 130 is a substantially planar film having an upper surface bonded to the first layer 110 and a lower surface bonded to the second layer 120. In some embodiments, the polymer interlayer 130 can have a thickness of up to about 3 millimeters. In some embodiments, the thickness of the polymer interlayer 130 can range from about 50 micrometers to about 1 millimeter. In other embodiments, the thickness of the polymer interlayer 130 can range from about 50 micrometers to about 5 millimeters. It is understood that the laminate structure can include additional layers, and that these layers can have various thicknesses, lengths, and widths. In other embodiments, the composition can be molded into various shapes using various types of molding, such as, for example, injection molding.
[0018] In some embodiments, the polymer interlayer 130 is a TPU. The TPU polymer can be formed by reacting a polyol with a polyisocyanate. The polyol can include polyester polyols, polyether polyols, polycarbonate polyols, and polycaprolactone polyols. In some embodiments, the polyol can be based on polycaprolactone. In another embodiment, the TPU can be an aliphatic polycaprolactone-based thermoplastic polyurethane. In some embodiments, the polymer interlayer 130 can include a semi-IPN formed from an aliphatic TPU using one or more RDMO additives crosslinked by peroxide free radicals. For example, the aliphatic TPU can be ELASTOLLAN® provided by BASF SE, Ludwigshafen, Germany. In some embodiments, suitable RDMOs include: acrylates, methacrylates, polyhedral oligomeric silsesquioxanes (POSS), and triallyl isocyanurates (TAIC). The acrylate and methacrylate monomers or oligomers can be monofunctional or multifunctional. In some embodiments, the acrylate or methacrylate is simply multifunctional. In some embodiments, the multifunctional acrylate or methacrylate has up to six functional groups. In some embodiments, the methacrylate or acrylate is a difunctional methacrylate, a difunctional acrylate, or a trifunctional acrylate pentaerythrityl triacrylate (PETA). In some embodiments, the POSS is an inorganic silsequioxane with an organic vinyl group attached to the core, an inorganic silsequioxane with an organic methacrylate group attached to the core, or an inorganic silsequioxane with an organic isooctyl group and three active silanol functional groups attached. In some embodiments, the TAIC is a trifunctional TAIC.
[0019] In some embodiments, the polymer interlayer 130 may have a Young's modulus of at least 25 MPa for a load duration of 1 second at 30° C. using the ASTM D4065 standard test method. In some embodiments, the polymer interlayer 130 may have a Young's modulus of at least 6 MPa for a load duration of 1 month at 30° C. In some embodiments, the polymer interlayer 130 may have a Young's modulus of at least 4 MPa for a load duration of 1 second at 60° C. In some embodiments, the Young's modulus may range from about 1.5 megapascals (MPa) to about 23 MPa for a 3 second load duration test performed at 30° C. In some embodiments, the polymer interlayer 130 may have a Young's modulus ranging from about 5 MPa to about 40 MPa. In some embodiments, the polymer interlayer 130 may have a Young's modulus ranging from about 15 MPa to about 35 MPa. Table 2 shows Young's modulus values for some embodiments of compositions for some modified TPUs over various lengths of time at 30° C. Table 3 shows Young's modulus values for some embodiments of compositions for some TPUs under load at 60° C. over various lengths of time.
[0020] According to another exemplary embodiment, a method of making the composition is provided. The method may include mixing the thermoplastic polyurethane, the second component, and the free radical curing agent together, for example, by twin-screw extrusion. Of course, it is understood that other mixing techniques may be used. For example, single-screw extrusion may be used. The addition of the second component and the curing agent may be performed using conventional melt compounding methods, such as, for example, using a Farrel continuous mixer (FCM™), a CW Brabender roller blade mixer, or by twin-screw extrusion.
[0021] In some embodiments, when small-scale or laboratory-scale modification of TPU is desired, the method of modifying TPU may include melting the TPU at a temperature of up to about 120° C., dosing the RDMO component to the TPU such that each dose is incorporated before the next dose is added, and mixing the TPU and the second component for at least 5 minutes using a mixer. In some embodiments, the curing agent may be added after or simultaneously with the addition of the RDMO using the same method. In other embodiments, such as when large-scale commercial-scale TPU modification is desired, other mixing methods may be used, including twin-screw extrusion. In some embodiments, the method may include using a scorch inhibitor to stabilize the RDMO for extrusion if thermal stability is an issue, as evidenced by crosslinking in the extruder.
[0022] In some embodiments, the RDMO can range from about 3% to about 60% by weight of the composition. In some embodiments, the RDMO can be one or more of: 20% monofunctional acrylate, 5% inorganic silsequioxane at the core and with organic vinyl groups attached, 5% inorganic silsequioxane at the core and with organic methacrylate groups attached, 20% difunctional, 20% difunctional acrylate, 20% trifunctional acrylate PETA, 20% trifunctional TAIC, and blends thereof. In some embodiments, the RDMO can range from about 3% to about 60% by weight of the composition. In some embodiments, the RDMO can range from about 3% to about 60% by weight of the composition. In some embodiments, the RDMO can range from about 3% to about 60% by weight of the composition. In some embodiments, the RDMO can range from about 3% to about 60% by weight of the composition. g In some other embodiments, the RDMO may have a T greater than about 60 degrees Celsius. g In some other embodiments, the RDMO may have a T greater than about 85 degrees Celsius. g In some other embodiments, the RDMO may have a T greater than about 110 degrees Celsius. g may have the following structure:
[0023] In some embodiments, the method can include extruding the TPU modified with the RDMO and curing agent. In some embodiments, the method can include blending the TPU with the RDMO and curing agent simultaneously, for example in a mixer. The blending can be done through gravimetric addition or other conventional methods. In some embodiments, the blending can be done at a temperature greater than about 100 degrees Celsius. In some embodiments, the blending can be done at about 120 degrees Celsius. In some embodiments, the blending can be done at about 140 degrees Celsius if thermal stability can be maintained to prevent crosslinking, for example by compounding the TPU with a thermally stable component. In other embodiments, the method can include extruding the TPU mixed with the RDMO and blended with the peroxide. In some embodiments, the method can include cooling the extrudate, for example to room temperature. In some embodiments, the method can include pelletizing the TPU using conventional TPU pelletizing methods. In some embodiments, the processing temperature is minimized to maintain the stability of the peroxide free radical initiator while allowing the extrusion of the TPU. Some RDMOs are monomeric and therefore have a low molecular weight, which causes them to behave like plasticizers in the TPU, reducing the melt viscosity of the compound (increasing its melt flow) so that lower processing temperatures can be used.
[0024] In some embodiments, the curing agent may be a peroxide, the selection being based on the half-life temperature of the peroxide at the processing temperature. In some embodiments, the peroxide may be 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, di(t-butyl)peroxide, or 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, which have half-lives of 1 hour at 151.8° C., 149.1° C., and 140.3° C., respectively. Other suitable peroxides may include 2,3-dimethyl-2,3-diphenylbutane, tert-butyl hydroperoxide, tert-amyl hydroperoxide, cumyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropyl cumyl hydroperoxide, isopropyl cumyl hydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.
[0025] In other embodiments, the curing agent may be a photoinitiator such as 2-hydroxy-2-methyl-1-phenylpropane, 1-hydroxycyclohexyl-phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane, 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,2-dimethoxy-2-phenylacetophenone, ethyl(2,4,6-trimethylbenzoyl)-phenylphosphinate-L, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. In yet other embodiments, the curing agent may be a compound with a diazenyl functionality (azo compound).
[0026] In some embodiments, the method may include flattening the extrudate, such as by pressing, compression molding, or other suitable processing. In some embodiments, the molding or flattening occurs immediately after blending. In some embodiments, the flattened or molded extrudate is cooled, for example to room temperature. In some embodiments, the method may include forming a laminate structure using the flattened extrudate. In some embodiments, the flattened extrudate is a layer between two glass layers (e.g., layers 110 and 120). In other embodiments, the flattened extrudate is a layer between two release liner layers, such as fluorinated ethylene propylene (FEP) release liners. In some embodiments, two release liners with the flattened extrudate as an intermediate layer are themselves between two glass layers. In some embodiments, the method includes bonding a top surface of the extrudate to a first glass layer and bonding a bottom surface of the extrudate to a second glass layer.
[0027] In some embodiments, the method may include curing the laminated structure formed with the extrudate. For example, the laminated structure may be sandwiched between a release liner and glass and cured in a vacuum laminator with a standard lamination cycle. In some embodiments, these lamination cycles are believed to include typical cycle procedures known to those skilled in the art. In other embodiments, the lamination and curing method may be performed using an autoclave or a vacuum kiln. In one embodiment, the lamination and curing process using a vacuum bag and an autoclave may include the following: performing a 15 minute vacuum step on the vacuum bag sealed laminate at room temperature and atmospheric pressure, followed by a 30 minute temperature ramp to 90°C with a pressure of ≧2 Bar; melting at 90°C for 90 minutes while maintaining a pressure of ≧2 Bar; ramping from 90°C to 150°C in 60 minutes; curing at 150°C; and cooling from 150°C to ambient temperature while maintaining a pressure of ≧2 Bar until cooling is complete. The description of the present invention is not limited with respect to the specific embodiments described in this application, but is intended as an illustration of various aspects. Many modifications and variations can be made without departing from its spirit and scope, as will be apparent to those skilled in the art. EXAMPLES
[0028] Example 1 Pellets of TPU Elastollan®, an aliphatic polyurethane purchased from BASF (Ludwigshafen, Germany, product number L1275A10), were melted in a CW Brabender Instruments, Inc. roller blade mixer (South Hackensack, NJ, USA) with the Brabender® processing temperature set at 120°C. The molten TPU was mixed in the Brabender® at 25 rpm. The TPU was then combined with a small amount of the second component to produce the modified TPU formulation. Table 1 shows a complete list of all the formulations (including the corresponding second component) produced in these experiments. In addition to the additives in Table 1, each of the formulations also contained 1.5% by weight of peroxide.
[0029] [Table 1] To achieve small laboratory scale mixing of RDMO into TPU, each dose of additive was incorporated into the molten TPU before the next dose was added. This was repeated until the target weight percent of additive was reached according to Table 1. The additive was homogenized in a mixer for a minimum of 5 minutes. The mixer rotation speed was adjusted to maintain the melt temperature at or below 120°C, and the peroxide was added to 1.5% by weight of the final composition. The peroxide was also homogenized in the mixer. The selection of the peroxide was based on the half-life temperature of the peroxide relative to the processing temperature. For the formulations listed in Table 1, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne was used as the peroxide agent. (Preferred peroxides include 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, di(t-butyl)peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, which have one hour half-lives at 151.8°C, 149.1°C, and 140.3°C, respectively. It is understood that other curing agents may be used.
[0030] The well-mixed TPU was flattened as much as possible and cooled. It was then wrapped in aluminum foil and placed in a polyethylene (PE) bag to allow the trapped air to be removed at room temperature. The bag was marked with a permanent marker (Sharpie®) pen and transported to a laminator for further processing using conventional autoclave lamination methods. To assemble a 4" x 4" laminate, 5 grams of the modified TPU was pressed between a glossy polyethylene terephthalate (PET) and a steel plate at 225°F to obtain an approximately 25 mil film. The film was then placed between two layers of fluorinated ethylene propylene (FEP) (commonly used as a release liner to ensure removal of the modified TPU after curing). A glass layer was placed on the free surface of the FEP layer such that the final configuration was as follows: glass / FEP / modified TPU / FEP / glass.
[0031] The laminate was then cured in a vacuum laminator using a 60 minute cycle at 300° F. The cycle step included 10 minutes of evacuation from both the top and bottom chambers, and the remaining time was spent pressurizing the top chamber to full atmospheric pressure using partial atmospheric pressure while the laminate structure was maintained under vacuum in the bottom chamber, resulting in pressurization and curing of the modified TPU in the laminate. Table 2 provides typical starting conditions for vacuum bag and autoclave at 150° C. for laminating and curing the structural TPU-IPN.
[0032] [Table 2] The mechanical property of tensile strength (Young's modulus) was determined for the formulations in Table 1 using a Dynamic Mechanical Analyzer (DMA) under the ASTM D4065 standard test method. Young's modulus values are shown for several formulations in Table 3 below. Tests for Young's modulus at 30° and 60° C. were performed using time-temperature superposition (TTS) to determine load duration test results. Load duration tests were performed at 30° C. for 1 second, 3 seconds, 1 minute, 1 hour, 1 day, 1 month, and 10 years for all formulations where these tests were possible. BASF L1275A10 (unmodified) TPU served as a control.
[0033] The results for the 30°C test are summarized in Table 3. BASF L1275A10 (unmodified) TPU showed Young's modulus of 10.02 MPa, 8.69 MPa, 6.39 MPa, and 3.83 MPa at 1 s, 3 s, 1 min, and 1 month, respectively. Compared to the control TPU, higher Young's modulus values were observed for the following formulations: LR01936-05 (5% inorganic silsequioxane with 1.5% peroxide in the core and with organic methacrylate groups attached), LR01942-02 (20% difunctional acrylate with 1.5% peroxide), LR01942-03 (20% trifunctional acrylate PETA with 1.5% peroxide), and LR01942-04 (20% trifunctional TAIC with 1.5% peroxide). For example, in the 1 second test, the results for these four formulations were 18.34 MPa, 23.89 MPa, 25.04 MPa, and 18.45 MPa, respectively. LR01942-03, which contained 20% trifunctional acrylate PETA modified TPU, significantly outperformed BASF L1275A 10 unmodified TPU in the 1 month 30°C load sustained test at 6.58 MPa, with a 1.7 times higher Young's modulus compared to the control.
[0034] [Table 3]
[0035] Example 2 The formulations were also compared against a BASF L1275A10 unmodified TPU base polymer control in a 60°C Young's modulus test run for the duration shown in Table 4. The ASTM D4065 standard test method was also used for these tests. At the higher temperature, the BASF L1275A10 unmodified TPU showed 3.51 MPa at 3 seconds and 2.39 MPa at 1 hour. LR01942-03 also outperformed the control in this test, showing 3.62 MPa at 3 seconds and 2.86 MPa at 1 hour. The results for all compositions included in this analysis are shown in Table 3. Notably, LR01942-04, a formulation containing 20% trifunctional TAIC, provided the same Young's modulus value as the control at 2.39 MPa at 1 hour.
[0036] [Table 4] Due to the effect of crosslinking with peroxides, which may occur at higher temperatures, increasing the mixing temperature in the Brabender above 120°C was found to negatively affect the process for making all of the formulations except those containing POSS. For the POSS modified TPUs, even lower susceptibility to crosslinking was observed at higher mixing temperatures such as 140°C. At this point, the pre-structural TPU interlayer is fully compounded with the RDMO and any free radical oxide curing agents that remain unreacted (uncrosslinked). The appearance / aesthetics of the interlayer are identical to conventional TPU interlayers. The pre-structural interlayer is packaged as usual and shipped to a glass laminator for conventional autoclave lamination.
[0037] The glass lamination and curing of the structural TPU are accomplished simultaneously through standard lamination techniques. The lamination process is initiated by sandwiching the pre-structural interlayer between two glass lenses, then the composite laminate is vacuum bagged to remove trapped air and then processed through conventional autoclave lamination techniques to produce a safe glass laminate. The first step consists of initial degassing of the structural TPU at room temperature via a vacuum bag. The bagged laminate structure is then transferred to an autoclave and overpressurized to greater than one atmosphere at room temperature to eliminate air entrapment and prevent void formation during thermal processing. The laminate is then heated using a designed temperature profile that goes from room temperature through a controlled melting stage and then finally to a plateau at the targeted cure temperature. Once at the cure temperature, the core temperature of the laminate is maintained at the appropriate amount to initiate crosslinking (curing) of the internal peroxide free radical curative with the RDMO component of the TPU interlayer. Once cured, the laminate is cooled in a manner consistent with a cooling rate that minimizes haze formation. The final cured laminate structure is comprised of a crosslinked structural TPU (TPU / semi-IPN) interlayer that has enhanced structural properties relative to a standard TPU interlayer.
[0038] Although the compositions, laminates, and methods discussed herein have been described in detail herein according to certain preferred embodiments thereof, many modifications and variations may be made by those skilled in the art. Accordingly, the foregoing description should not be construed as limited thereby, but should be construed as including such obvious modifications as set forth above and limited only by the spirit and scope of the following claims.
Claims
1. Thermoplastic polyurethane (TPU); a second component in an amount ranging from about 3% to about 60% by weight of the composition; wherein the second component comprises at least one reactive diluent, monomer, or oligomer (RDMO); composition.
2. A first layer, a second layer of thermoplastic polyurethane (TPU) and a second component; the second component is in an amount ranging from about 3% to about 60% by weight of the second layer, and the second component comprises at least one reactive diluent, monomer, or oligomer (RDMO); Laminated structure.
3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component is selected from the group consisting of monofunctional acrylates, difunctional acrylates, trifunctional acrylates, monofunctional methacrylates, difunctional methacrylates, trifunctional methacrylates, acrylates or methacrylates having 4 to 6 functional groups, pentaerythrityl triacrylate, polyhedral oligomeric silsesquioxanes, and triallyl isocyanurate.
4. 3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component is crosslinked to form a semi-interpenetrating polymer network.
5. 3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component and the TPU are crosslinked to form an interpenetrating polymer network.
6. 3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component is about 20% by weight of the composition or second layer.
7. 3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component is about 5% by weight of the composition or second layer.
8. 3. The composition of claim 1 or the laminated structure of claim 2, wherein the second component is selected from the group consisting of difunctional acrylates, trifunctional acrylates, and trifunctional triallyl isocyanurate (TAIC), and trifunctional acrylate pentaerythrityl triacrylate (PETA).
9. 3. The composition of claim 1 or the laminate structure of claim 2, wherein the second component comprises a polyhedral oligomeric silsesquioxane.
10. The method of claim 1, wherein the second component comprises a polyhedral oligomeric silsesquioxane; 3. The composition of claim 1 or the laminate structure of claim 2, wherein the polyhedral oligomeric silsesquioxane comprises 5% by weight of inorganic silsesquioxane bonded to one of the group consisting essentially of vinyl groups, organic methacrylate groups, and organic isooctyl groups.
11. 11. The composition or laminate structure of claim 10, wherein the 5 wt. % inorganic silsesquioxane is bonded to an organic isooctyl group and further has three active silanol functional groups.
12. 10. The composition of claim 1, wherein the composition has a Young's modulus greater than about 10 for a 1 second load duration at 30°C.
13. The composition of claim 1 further comprising a curing agent.
14. The composition of claim 13, wherein the curing agent is selected from the group consisting of UV-activated photoinitiators, peroxides, and azo compounds.
15. The composition of claim 13, wherein the curing agent is a peroxide.
16. The composition of claim 1 , wherein the second component has a glass transition temperature of at least about 60 degrees Celsius.
17. The laminate structure of claim 2 further comprising a third layer, said second layer being disposed between said first and third layers.
18. The laminate structure of claim 2 , wherein the first and third layers comprise glass layers.
19. 20. The laminate structure of claim 18, wherein the second layer forms an interlayer between the glass layers and further comprises a release liner separating the interlayer and the glass layers.
20. A glass structure comprising the laminate structure of claim 2 .
21. A roof structure comprising the laminate structure of claim 2.
